Virtual Training via Vibrotactile Arrays - Bloomfield, Aaron; Badler, Norman I. (Presence : teleoperators and virtual environment, 2008)
What is often missing from many virtual worlds and training simulations is a physical sense of the confinement and constraint of the virtual environment. We present a method for providing localized cutaneous vibratory feedback to the user's right arm. We created a sleeve of tactors linked to a real-time human model; the tactors activate to apply sensation to the corresponding body area. The hypothesis is that vibrotactile feedback to body areas provides the wearer sufficient guidance to assume correct body configurations and ascertain the existence and physical realism of access paths. We present the results of human subject experiments that study both explicit and implicit training of skills using vibrotactile arrays. Implicitly, collision awareness is achieved by activating the appropriate tactor when a body part collides with the scene; thus, the user will attempt to correct his or her body configuration. Explicitly, we use the tactors to guide the body into the proper configuration. The results of human subject experiments clearly show that the use of full arm vibrotactile feedback improves performance over purely visual feedback for navigating the virtual environment, as well as allowing easy acquisition of new skills. These results validate the empirical performance of this concept.